THE ANALYSIS OF SEISMOTECTONICS, PERIODICITY, AND CHANGING OF QUAKES LEVEL IN WEST NUSA TENGGARA AREA BASED ON 1973 – 2015 DATA - Istiqomah, Melinda Utami; Sunardi, Bambang; Marzuki, Marzuki; Minardi, Suhayat (Universitas Mataram, 2019)
This research was conducted as one of the earthquake disaster mitigation efforts in Nusa Tenggara Barat region, because this region is one of the regions in Indonesia which has a relatively high level of seismicity. The purpose of this research is to determine seismotectonic parameter, earthquake periodicity along with the average of seismicity rate changes in Nusa Tenggara Barat region. The data used in this research is the data sourced from the United States Geological Survey (USGS) and Badan Meteorologi Klimatologi dan Geofisika (BMKG) from Januari 1973 until February 2015 for Bali Strait region up to Banda Sea with coordinate boundaries of 1140–1300 East Longitude and 40-130 South Latitude. This research was conducted using the maximum likelihood method with second party of software Zmap ver 6.0 also software ArcGis ver 10 to map seismotectonic parameter, periodicity and the average velocity of seismicity rate changes. Variation b value range between 0.972–1.44, a low value of b are associated with high stress levels, and vice versa. The a value range between 6.67- 9.1, its show that the regions with high a value experience a relatively high earthquake incidence rate, and vice versa. The density of earthquake is about -2.63 to -2.01 logN/km2 or the occurrence of earthquakes in the area is very rare. Earthquake periodicity with magnitude (M) 6 SR is 5 to 18 year, M 6.5 SR is 16 to 67 year, M 7 SR is 54 to 304 year, and M 7.5 SR is 178 to 1.386 year. The average of seismicity rate changes on a case that occurred in Sumbawa in 1982 is more than 125%, meanwhile the earthquake that occurred in 2009 is more than 75%.Copyright © 2019IPR. All rights reserved.